(untitled) (Revista de Administração, 2007)
The question of the quality of life in the work has been raising the countless researchers' attention, but the literature of the area lacks reliable measurement instruments. This article describes the construction process and validation of a scale to evaluate the satisfaction perception with the quality of life in the context of the work, based on the theoretical model of Hackman and Oldham (1975) and in lifted up aspects in a previous research with 25 military of the Secretary of Economy and Finances (integrant Organ of the High Administration of the Army) and of their Military Organizations directly subordinates, located in Federal District. The built items, after the judges' analysis and semantics, were applied to a sample of 300 individuals of the same organizations. Their answers were submitted to the factorial analysis, with promax rotation, with internal consistence, producing a structure with four factors, thoroughly backed in the literature of the area, which explained more than 48% of the variance of the phenomenon. Of the four factors, two presented great reliability index (Alpha of Crombach), while the others can only be considered promising. The scale, denominated of Contextual Satisfaction Indicator Scale, CSIS, can contribute to the identification of aspects that must be developed in the organizational atmosphere, but it must be submitted to new applications that guarantee larger generality to the found results.